EVALUASI STANDAR SARANA DAN PRASARANA LAPANGAN OLAHRAGA DI SEKOLAH SD NEGERI 207 LEMO LEMO - Ilham Febriansyah; Andi Sri Rafiqa Hayu; Alim Nur; Ilham Febriansyah; Muh. Iksan; Muh. Sulpadli (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to evaluate the conformity of sports facilities and infrastructure at SD Negeri 207 Lemo Lemo with the standards established by the Minister of National Education Regulation and national sports organization provisions. The main problem addressed is the gap between the factual condition of sports facilities in elementary schools in remote areas and the minimum standards that should be met to support the learning process of Physical Education, Sports, and Health (PJOK). The research method used is descriptive qualitative with a field survey approach. Data collection techniques include direct observation, documentation, interviews with the principal, PJOK teachers, and students, as well as filling in checklist instruments based on Permendiknas Number 24 of 2007. The results show that most sports facilities and infrastructure at SD Negeri 207 Lemo Lemo do not meet the established standards, both in terms of quantity and quality. The main sports field does not have appropriate dimensions, PJOK learning equipment is in unusable condition, and there are no changing rooms or sports equipment storage facilities. This condition hampers the achievement of students' basic competencies in PJOK subjects. This study recommends that local governments and schools prioritize the procurement and maintenance of sports facilities as a long-term investment in improving the quality of physical education.